Skeletal Muscle Regeneration: Functional Skeletal Muscle Regeneration with Thermally Drawn Porous Fibers and Reprogrammed Muscle Progenitors for Volumetric Muscle Injury (Adv. Mater. 14/2021). Issue 14 (7th April 2021) - Jin, Yoonhee; Shahriari, Dena; Jeon, Eun Je; Park, Seongjun; Choi, Yi Sun; Back, Jonghyeok; Lee, Hyungsuk; Anikeeva, Polina; Cho, Seung‐Woo
Abstract : In article number 2007946, Polina Anikeeva, Seung‐Woo Cho, and co‐workers develop a hybrid muscle construct for skeletal muscle regeneration using synthetic polymer scaffolds engineered with decellularized muscle extracellular matrix and induced skeletal myogenic progenitor cells. Thermally drawn fiber scaffolds modified with muscle extracellular matrix provide the optimal mechani cal robustness and biochemical cues for reprogrammed muscle tissue. Engraftment of the bioengineered muscle construct induces de novo muscle regeneration and functional recovery.